2011
DOI: 10.1007/s11368-011-0438-0
|View full text |Cite
|
Sign up to set email alerts
|

The interpolation accuracy for seven soil properties at various sampling scales on the Loess Plateau, China

Abstract: Purpose Knowledge of the changes in interpolation accuracy with changing sampling scales is important when designing an appropriate sampling strategy. The objectives of this study were (1) to analyze the changes in interpolation accuracy with changing sampling scales for seven soil properties and (2) to find a suitable index that could predict the interpolation accuracy well. Materials and methods Nine hundred sixty-one samples were collected from a 30×30-m area. Seven soil properties were measured for each sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A geostatistical approach can be used to study spatial dynamics of soil moisture. The MLR‐RK or RBFNN‐RK method has been used in several studies to interpolate SMC for the top soil layer at small spatial scales on the CLP (Gao & Shao, 2012; Yao et al., 2013). Only a few SMC interpolations have been down at regional scales or for diverse soil layers using two methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A geostatistical approach can be used to study spatial dynamics of soil moisture. The MLR‐RK or RBFNN‐RK method has been used in several studies to interpolate SMC for the top soil layer at small spatial scales on the CLP (Gao & Shao, 2012; Yao et al., 2013). Only a few SMC interpolations have been down at regional scales or for diverse soil layers using two methods.…”
Section: Discussionmentioning
confidence: 99%
“…The MLR‐RK method of interpolation of SMC was not very suitable, compared with the other methods. This indicated that the MLR‐RK method was not suitable for SMC interpolation at regional scale (Gao & Shao, 2012; Shen et al., 2019; Yao et al., 2013). The method considers structural and random factors of soil property distribution and thereby enhances interpolation accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Soil moisture is highly and nonlinearly variable in both time and space due to heterogeneity of climate and soil across different scales (Heathman et al, 2012). Studies have identified important spatiotemporal variability characteristics of SWC from different aspects, such as the spatio-temporal patterns of SWC (Cantón et al, 2004;Brocca et al, 2007), the relationship between the heterogeneity and its mean values (Hupet and Vanclooster, 2002;Choi and Jacobs, 2007), the spatial scaling of SWC (Western and Blöschl, 1999;Gao and Shao, 2012a), and the controlling factors of spatio-temporal patterns (Gómez-Plaza et al, 2001;Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of Yan'an urban forest are as follows: (a) By the end of 2015, the total area and coverage rate of forests and trees in the study area was 1016.64 km 2 (suburb forests = 998.76 km 2 , urban green spaces = 16.73 km 2 , street trees = 1.15 km 2 ) and 65.8%, respectively. (b) The soil parent material is relatively homogeneous, the soil type is mainly loessial soil and the thickness ranges from approximately 50 m to 200 m [ 44 ], the soil has been deposited by the wind since the Quaternary period [ 45 ]. (c) However, the water retention properties of loessial soil are very poor because of its low anti-scourability [ 43 ].…”
Section: Methodsmentioning
confidence: 99%